520 AN EVALUATION OF VIRTUAL MUSIC THERAPY TO PATIENTS ON AN ACUTE HEALTH CARE OF OLDER PEOPLE WARD DURING THE COVID-19 PANDEMIC. (14th June 2021) - McAulay, J; Block, M; Booth, V; Cowley, A
Abstract: Introduction: Music therapy has been shown to reduce anxiety and social isolation for elderly patients in the acute hospital setting. At Nottingham University Hospital NHS Trust a programme of live, face-to-face music has been delivered by Wellspring Music on Healthcare of Older Peoples wards since 2015. In response to COVID-19, face-to-face delivery was stopped and a virtual method was proposed. This project investigated feasibility of virtual live music delivery. Method: Twelve, two-hour music therapy sessions were delivered by Wellspring Music to 41 patients over six weeks. The validated Arts-obs tool was used by staff members facilitating the sessions to record observations of patient mood, relaxation, and distraction from the ward setting on Likert scales. Patient, ward staff, and facilitator feedback were also recorded. Qualitative and quantitative analyses were conducted by an Occupational Therapist. Results: Data from the Arts-obs tool showed that thirty-two patients had an observable improvement in mood, seven had no mood change, and two presented a slightly worsened mood. Fourteen patients were fully engaged with the music therapy, sixteen were partially engaged, and eleven were focussed on the hospital environment. Thirty-four patients were visibly more relaxed, and seven showed no change. Patient feedback ranged from gratitude and expressions of enjoyment of the session to finding it too loud. Ward staff feedback ranged from appreciation to finding the music too distracting. The Wellspring musician and staff facilitators reported occasional loss of internet connection, and patients sometimes focusing on the facilitator rather than the musician. Conclusion: It is feasible to deliver virtual music therapy to inpatients on Health Care of Older People wards. Feedback shows that this was largely acceptable to staff and patients. Improvements in mood, relaxation and distraction were found.